Compression Image by Using Iterated Function Systems - Basil Al-khayat; Mahasin Younis (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research was in the compression digital images using the iterative function and applied to grayscale images, color images and then re-pressed image decoding. Matlab language is used for programming the system, the proposed algorithms have been applied to a number of images and the results show the efficient and accurate of the proposed algorithms. The method of compressing using iterative function systems methods are from loss compressing methods the advantage of these method by high compressing rate and this was confirmed by the results obtained have been getting a good percentage of the compressing and the quality is good and clear.